Comparative Variation of Biochemical Parameters in Cultural and Natural Fishes Indian Major Carps - Saravanan, K (International Journal of Pharmaceutical & Biological Archive, 2014)
Comparative Variation of Biochemical Parameters in Cultural and Natural Fishes Indian Major Carps